Where do pre-service teachers' educational psychological misconceptions come from?: the roles of anecdotal versus scientific evidence - Menz, Cordelia; Spinath, Birgit; Seifried, Eva (Zeitschrift für pädagogische Psychologie, 2021)
Previous research has found a high prevalence of some (educational) psychological misconceptions (i.e., incorrect but often popular assumptions that contradict results from psychological research) among (pre-service) teachers. However, the number of topics that have been investigated is limited. Additionally, knowing the sources of misconceptions might be helpful for rebutting them. Furthermore, anecdotal evidence has been found to be important for informing (pre-service) teachers' practice, but personal experiences also are among the main sources of misconceptions. Therefore, we hypothesized that pre-service teachers would predominantly view sources of anecdotal evidence as the origin of their educational psychological beliefs in general and the main source of their misconceptions in particular. In an online survey (with correlational and quasi-experimental elements) of N = 836 pre-service teachers, we found that educational psychological misconceptions were less prevalent than expected but that pre-service teachers indeed mainly based their beliefs on sources of anecdotal evidence (personal experiences and narratives from other people) and that these nonscientific sources turned out to be the main sources of their misconceptions (comparison with scientific sources: d = 0.19 and d = 0.23). Furthermore, referring more to sources of anecdotal than scientific evidence (research and lectures) was associated with undesirable aspects, that is, more misconceptions (d = 0.21) and less reduction of misconception endorsement through empirical refutation-style information (d = 0.30) but not with a lower judgment of the view that it is possible to examine educational psychological topics scientifically. In sum, our results indicate that basing one's beliefs more on sources of anecdotal than scientific evidence is associated with outcomes that stand in contrast to evidence-based education. Future research should investigate why pre-service teachers concentrate on sources of anecdotal evidence, how to make sources of scientific evidence more tempting, and whether counteracting misconceptions by showing the downside of nonscientific sources is effective.